A Simple and Reliable Submental Intubation Technique for Maxillofacial Fractures. Issue 7 (October 2018) - Oshima, Naoya; Shiraishi, Tomohiro; Kawauchi, Tsukasa; Oba, Jun; Sato, Daisuke; Fujiki, Masahide; Ozaki, Mine; Takushima, Akihiko; Harii, Kiyonori
Abstract : Abstract: In 1986, Altemir first reported the use of submental intubation to avoid tracheotomy in patients with panfacial and midfacial fractures for whom intermaxillary fixation is necessary, but orotracheal and nasotracheal intubations are not recommended. This novel technique allowed intraoperative access to perform dental occlusion and reconstruction of the nasal pyramid in patients with skull base fractures. Herein, we describe a refined technique based on Altemir's original procedure. Seven male patients with panfacial fractures underwent submental intubation using our refined technique. The technique was developed after encountering a technical error with Altemir's original procedure. In this new technique, we employed a 2-0 silk suture guide to allow the passage of both the endotracheal and cuff-inflation tubes through the same tunnel created from the oral cavity to the submental area. The success rate of the refined technique was 100%, and there were no intraoperative or postoperative complications. There was 20 seconds of ventilation outage time in total. Endotracheal and cuff-inflation tubes were easily and quickly passed through the same submental tunnel. Our refined technique is simple, easy, safe, fast, inexpensive, and does not require specific materials. Submental scars were smaller and relatively inconspicuous in this study, compared to those reportedly associated with other modified techniques. Abstract : Supplemental Digital Content is available in the text